(untitled) (Revista Iberoamericana de Bioética, 2017)
We are all dependent persons and from this limitation and human condition we can find some deep insights to better understand vulnerability as a principle of bioethics. This article introduces the concept of dependence as outlined by the Scottish philosopher, settled in the United States since 1971, Alasdair MacIntyre in his work Dependent Rational Animals. From this work, we want to rehabilitate the importance of dependency in the life of every living being and we want to propose some basic ideas so as to gain a better understanding of the principle of vulnerability.